Assessment of Non Communicable Diseases Awareness Among Pupils with hearing impairment at Munali High School in Lusaka, Zambia - Irwin Kabinje Mawani; Brian Chanda Chiluba (Indonesian Journal of Disability Studies, 2020)
Among the neglected population in NCD awareness is the population of people with hearing impairment or deaf. Little effort is made to ensure that people are deaf are covered in these NCDs awareness programs. Hence this study aimed at assessing the NCDs awareness among people who are deaf in Zambia, particularly assessing the knowledge of NCDs risk factors, diagnosis and treatment. The study utilized a phenomenological study type with were 10 participants who were purposively sampled. 5 males and 5 females were chosen, 2 from Grade ten, 4 from Grade eleven and 4 from Grade twelve. These were chosen because of their ability to adequately read and understand English language. The study highlighted that among the many factors, the major factors were identified as; lack of communication between the health personnel and the deaf person (pupil), attitude (stigma) of the health personnel towards the person who are deaf (pupil), lack of health education in the school curriculum and lack of specific information on NCDs. Other identified factors were lack of regular health campaign within the school premises, lack of health materials on NCDs and poor organization of physical education.some issues such as lack of communication between the health personnel and them, the attitude of the health personnel, lack of health education in the school curriculum and lack of specific information on NCDs were found to be the major cause of low awareness among the target